The Role of Mycorrhizae on the Growth of Banana Planlets of Cultivar Raja (Musa Paradisiaca C.V. Raja) from Bali at Post Acclimatization: Role of Mycorrhizae on the Growth of Banana Planlets - Dwiyani, Rindang; Wirya, Gusti Ngurah Alit Susanta; Gunadi, I Gusti Alit; Darmawati, Ida Ayu Putri; Yuswanti, Hestin; Susrusa, Ketut Budi; AStiningsih, Ana Agung Made (Journal of Tropical Life Science, 2024)
The effect of inoculation of a combination of the arbuscular mycorrhizal fungus of Glomus and Acaulospora on micropropagated banana plantlets cultivar Raja from Bali during the acclimatization phase was investigated. The experiment was conducted at the Experimental Station of the Faculty of Agriculture, Udayana University, Denpasar, Bali, Indonesia, over the period of March to June 2022. The objective of this research was to evaluate the impact of various doses of mycorrhizae on the growth of tissue culture banana plantlets that had undergone acclimatization for a period of six weeks. A total of five different doses of mycorrhiza were applied to the acclimatized plantlets, namely M0=without mycorrhiza and M5=5g mycorrhiza.kg-1, M10=10 g mycorrhiza.kg-1, M15=15 g mycorrhiza.kg-1, M20=20 g mycorrhiza.kg-1. A significant effect was discovered at M15; however, compared to M20, M20 gave better results for root length and fresh weight of the above-ground part, indicating the best dose was 20 g mycorrhiza kg-1. This study concluded that mycorrhiza has a very significant role in supporting the growth of micro propagated banana plantlets at post-acclimatization. Variables observed, such as the average number of leaves, stem diameter, above-ground plant fresh and dry weight, and root fresh and dry weight, increased with the application of AMF (Glomus and Acaulospora).